Cleveland Coal Show (1947) - Hercules Incorporated (1947)
General view of the Hercules Powder Company display at the 1947 Cleveland Coal Show held at the Cleveland Public Auditorium. Formed in 1912 as part of an anti-trust settlement with DuPont, the Hercules Powder Company (later Hercules Inc.) initially specialized in the manufacture of explosives and smokeless powders and subsequently diversified its business to encompass a variety of industrial products, including pine and paper chemicals, synthetics, pigments, polymers, and cellulose.
Keywords: Hercules Incorporated; Trade shows; Corporations; Chemical industry; Explosives; Explosives industry; Advertising; Advertising, Industrial